Design for voice interfaces - Klein, Laura (O'Reilly Media, 2015)
Keyboards and input screens still work for mobile devices, but they just might disappear for some wearables and IoT devices. How viable is voice interface as an alternative? This O'Reilly report looks into recent advances in computing power and natural language processing (NLP), as well as the skills necessary to create intuitive, discoverable voice interfaces that users can navigate with ease. Voice interfaces have been around, at least in our imaginations, long before Captain Kirk addressed the Enterprise's shipboard computer. Author Laura Klein covers the past, present, and future of voice interfaces, and shows you how to take advantage of recent advances--and tackle existing problems--to produce a viable user experience design for voice. Learn the state of the art in NLP (Watson, Siri) and voice recognition (Android) Understand problems engineers face with discoverability and navigation Delve into different voice interface use contexts, including privacy, interactivity, and mobility (in moving vehicles) Use voice naturally with other input methods, such as swiping, tapping, gestures, and physical buttons Make users feel secure, let them easily recover from mistakes, and help them make voice input a habit Learn how voice input is being used with IoT devices.